IMPLEMENTATION OF CURRICULUM MANAGEMENT IN THE FORMATION OF STUDENTS' RELIGIOUS CHARACTER AT RA ISLAM AN-NAAS - Yulianti; Saprin; Shabir Umar (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
The formation of religious character in early childhood has become a central concern in Islamic education, especially in responding to rapid social and cultural changes. Schools are increasingly expected to deliver academic knowledge and shape values that guide children’s behavior and identity. This research explored how curriculum management contributes to cultivating religious character among students at RA Islam An-Naas Cakura, Takalar. Adopting a qualitative phenomenological design, this study involved teachers, school leaders, and parents as participants, selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and documentation, with the researcher as the primary instrument supported by field notes and recording tools. The findings reveal three main themes: integrating Islamic values into the curriculum, habituating religious practices such as prayer and Qur’an recitation, and the central role of teachers’ modeling reinforced by parental support at home. Challenges such as inconsistent parental involvement and limited facilities emerged as significant barriers. This study concludes that effective curriculum management for character education relies on continuous collaboration between schools, families, and communities. Its contribution lies in extending character education theory by contextualizing it within Islamic early childhood education, while practically offering a model that strengthens home–school synergy in religious formation.